The Pharmacokinetic Drug-Drug Interactions of Andrographis paniculata and Ibuprofen in the Plasma of Healthy Oryctolagus cuniculus Rabbits - Mutakin Mutakin; Sandra Megantara; Batari A. Larasati; Yogiyanto Yogiyanto; Jutti Levita; Slamet Ibrahim (Pharmacology and Clinical Pharmacy Research)
An HPLC method was developed and validated for the pharmacokinetic drug-drug interaction between Andrographis paniculata and ibuprofen in the plasma of Oryctolagus cuniculus rabbits after a single oral administration of the mixture. Nine healthy rabbits (6 males and 3 females, weight 1.68-2.42 kg) were acclimatized for 7 days and were randomly divided into 3 groups. At day-8th the rabbits were group (1) treated with a single oral administration of ibuprofen (dose of 28 mg/kg BW); group (2) treated with a single oral administration of Andrographis paniculata infusion (7.04 mL/kg BW); group (3) treated with a single oral administration of a mixture of Andrographis paniculata (7.04 mL/kg BW) infusion and ibuprofen (dose of 28 mg/kg BW). Plasma samples were prepared by collecting the blood from the marginal ear vein at 0, 30, 60, 90, and 120 minutes after the mixture administration, followed by centrifuging it for 30 minutes 3000 rpm. Chromatographic separation was performed on a LiChrosorb RP-18 with methanol and double-distilled water (70:30) as the mobile phase, flow rate 1 mL/minute. UV detection was set at 227 nm. The absorption and distribution of ibuprofen were fast (Tmax = 30 min; Cmax = 4.02962 mcg/mL), however, interestingly this drug could improve the absorption and distribution of andrographolide in Oryctolagus cuniculus rabbits